Breakdown of intention-based outcome evaluation after transient right temporoparietal junction deactivation - Junfeng Zhang; Sai Sun; Chengyan Zhou; Yaochun Cai; Hao Liu; Zhaoyang Yang; Rongjun Yu (Scientific Reports, 2023)
Abstract People judge the nature of human behaviors based on underlying intentions and possible outcomes. Recent studies have demonstrated a causal role of the right temporoparietal junction (rTPJ) in modulating both intention and intention-based outcome evaluations during social judgments. However, these studies mainly used hypothetical scenarios with socially undesirable contexts (bad/neutral intentions and bad/neutral outcomes), leaving the role of rTPJ in judging good intentions and good outcomes unclear. In the current study, participants were instructed to make goodness judgments as a third party toward the monetary allocations from one proposer to another responder. Critically, in some cases, the initial allocation by the proposer could be reversed by the computer, yielding combinations of good/bad intentions (of the proposer) with good/bad outcomes (for the responder). Anodal (n = 20), cathodal (n = 21), and sham (n = 21) transcranial direct current stimulation (tDCS) over the rTPJ were randomly assigned to 62 subjects to further examine the effects of stimulation over the rTPJ in modulating intention-based outcome evaluation. Compared to the anodal and sham stimulations, cathodal tDCS over the rTPJ reduced the goodness ratings of good/bad outcomes when the intentions were good, whereas it showed no significant effect on outcome ratings under unknown and bad intentions. Our results provide the first evidence that deactivating the rTPJ modulates outcome evaluation in an intention-dependent fashion, mainly by reducing the goodness rating towards both good/bad outcomes when the intentions are good. Our findings argue for a causal role of the rTPJ in modulating intention-based social judgments and point to nuanced effects of rTPJ modulation.